Surveillance for Antimicrobial-resistant Organisms in Infants Transferred to the Neonatal Intensive Care Unit: Trends in Colonization and Practices. (4th October 2017) - Duchon, Jennifer; Maykowski, Philip; Good, Pamela; Kytomaa, Sonja; DeLaMora, Patricia; Saiman, Lisa
Abstract: Background: Infections with antibiotic-resistant organisms (AROs), i.e., methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and multi-drug-resistant Gram-negative rods (MDR-GNR) among infants hospitalized in the Neonatal Intensive Care Unit (NICU) are associated with mortality and serious morbidities. Implementing appropriate infection control policies may help prevent transmission of AROs. However, the most effective strategies for surveillance of AROs in the NICU are unclear. Prior data collected from infants transferred from outside hospitals to 2 NICUs affiliated with New York-Presbyterian (NYP) Hospital detected low rates of ARO colonization in the first week of life. Thus, in 2013 the strategy of performing surveillance on all transferred infants for AROs was changed to performing targeted surveillance on infants transferred at >7 days of life (DOL). The purpose of this study was to assess this change in surveillance strategy and monitor ARO colonization trends in the NICU. Methods: Data from all infants transported to the NICUs at NYP from 2007 to 2016 were used. Risk factors for colonization with AROs including demographics and admitting diagnoses were explored using a multivariable binomial mixed model clustered by transferring hospital and controlled for NYP NICU. Trends in ARO colonization over time were assessed using negative binomial regression. Site 1 elected not to adopt the change in surveillance policy, and thus was used as a control. Results: From 2007 to 2016, 2925 infants were transferred to the NYP NICUs, 1101 at Site 1 and 1824 at Site 2; 2571 (88%) had surveillance for at least 1 ARO. There were 226 positive surveillance cultures in 204 infants (8%): 94 (3.7%) for MRSA, 78 (3%) for VRE and 54 (2%) for MDR-GNR. In the final models, transfer DOL remained a highly significant (OR per day = 1.018, CI95 1.014, 1.022, P < 0.001) predictor of colonization with any ARO. There was no significant increase in the incidence of transferred infants colonized with AROs over time in either NICU; this remained true in infants who were < 7 days of life at Site 1. Conclusion: These data continue to support the rationale for our change in surveillance policy. Further studies should evaluate the effect of this strategy on ARO transmission in the general NICU population. Disclosures: All authors: No reported disclosures.